SIMULASI PEMANFAATAN LAHAN BERDASARKAN PENDUGAAN EROSI TANAH: STUDI KASUS SUB DAS MOWEWE DI DAS KONAWEHA SULAWESI TENGGARA - Miranda R. Malamassam; Sandra E. Pakasi (Forestry Faculty of Universitas Hasanuddin, 2006)
Sub watershed of Mowewe has been considered as important regions in South East Sulawesi because it takes a great responsibility as a water supplier in Konaweha watershed. Konaweha watershed is a source of irrigation and domestic water for Kolaka Regency, Konawe Regency, South Konawe Regency and Kendari Municipality which have been recently in a critical condition. For this reason, it should be well managed. This study was implemented with the aim of establishing model of land use in Mowewe sub watershed that can preserve the land and water resources. The method employs a system analysis with simulation technique by using the Universal Soil Loss Equation (USLE) model based on Geographical Information Systems (GIS). The result of the research revealed that the predicting soil erosion is 68,58 ton/ha/year, more than the Tolerable Soil Loss (TSL) value of 21,52 ton/ha/year. Therefore, restructuring of land use pattern should be done to improve the condition of the area to achieve a sustainability. Keywords : Watershed, land use, soil erosion, GIS